The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1590/1807-3107bor-2022.vol36.0116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on gender gap in dental publications: a retrospective cohort with three Brazilian journals

Abstract: This was a retrospective cohort study to investigate the impact of COVID-19 pandemic on the gender gap in articles submitted to three international dental journals based in Brazil. All submissions performed to Brazilian Dental Journal, Brazilian Oral Research, and Journal of Applied Oral Science before (2019) and during the pandemic (2020) were assessed. Gender of the first, last, and corresponding authors were collected. Other variables collected were journal, continent studied by authors and stage of their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Reports have indicated negative consequences that disproportionately affect female researchers, in their early career stages, with intersecting identities, and those from countries deeply affected by COVID-19. 3,4,6,8 In contrast, our analysis demonstrated that the majority of first and last roles in authorship were women. This distribution can be observed in Brazilian Dentistry, in which women are the majority of registered dentists (61.0%) and dental researchers (55.4%).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Reports have indicated negative consequences that disproportionately affect female researchers, in their early career stages, with intersecting identities, and those from countries deeply affected by COVID-19. 3,4,6,8 In contrast, our analysis demonstrated that the majority of first and last roles in authorship were women. This distribution can be observed in Brazilian Dentistry, in which women are the majority of registered dentists (61.0%) and dental researchers (55.4%).…”
Section: Discussioncontrasting
confidence: 69%
“…6 In 2023 there are COVID-19 vaccines, however, the pandemic is still ongoing with outbreaks of infection caused by variants of interest emerging across the world, with impact on the provision of dental care and research. [7][8][9] Recent evidence has highlighted Brazilian contribution to dental research: Brazil has ranked second in the number of international publications in Dentistry for over fifteen years and ranked second in citations in 2017. 10 Held in Brazil, the Annual Meeting of the Brazilian Division of the International Association for Dental Research -Sociedade Brasileira de Pesquisa Odontológica (SBPqO), is the largest dental research conference in Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Franco et al highlighted how the COVID-19 pandemic decreased the proportion of women as corresponding authors in Central and South America [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Career interruptions for parental leave, childcare, and unavailability to travel are some of the reasons that can help to explain gender inequity 30 . Moreover, structural misogyny remains in several societies, and even women without children are less prone to achieve the highest positions in an academic career 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, most dentists are females in Brazil (only 43% are men) 1 , and a lower gender gap among the speakers at dental conferences would be expected. Prior studies have shown gender inequalities in scientific publications by Brazilian dental researchers 21 , 22 , but information about the gender gap among speakers at Brazilian dental conferences is currently unavailable. The present study assessed the prevalence of lectures involving esthetic topics and gender speakers in three major dental conferences held in Brazil between 2016 and 2020.…”
Section: Introductionmentioning
confidence: 99%